Оцінка ефективності вібраційної оздоблювально-зачищувальної обробки у резервуарах з мультиенергетичним впливом і різною формою поперечного перерізу - Міцик, А. В.; Федорович, Володимир Олексійович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Дана сутність і ефективність процесу мультиенергетичної вібраційної оздоблювально-зачищувальної обробки. Зроблено припущення, що ефективність віброобробки залежить від інтенсивності руху завантаження резервуара відносно його робочих поверхонь. Встановлено, що факторами цього руху є форма поперечного перерізу резервуара та поле його коливань. Наведено опис і вибір параметрів фізичної та динамічної моделей для визначення поперечного перерізу резервуара.

The nature and effectiveness of the process of multi-energy vibration finishing and grinding treatment is given. The assumption is made that the effectiveness of vibration processing depends on the intensity of the movement of the reservoir loading, relative to its working surfaces. It has been established that the factors of this movement are the cross-sectional shape of the reservoir and the field of its oscillations. A description and selection of the parameters of the physical and dynamic models of the process for determining the cross-section of the reservoir is given. The study of the dynamic model allows us to conclude that the shape of the transverse cut and the oscillation fields of the reservoir affect the speed of the circulating movement of its load and the magnitude of the forces acting in the load, which directly affects the efficiency of the vibrating process. It has been established that the greatest importance is the speed in the tank “rectangular” with rounded transitions from the bottom to the walls of the overcut shape, which do not change the cut geometry, but only exclude the stagnation of the mobile load. In a reservoir of this cross-cut shape, the forces acting in the load take the least value. Comparison of the intensity of changes in the roughness of the surface of parts treated in tanks of the studied cross-cut shapes with the parameters of the load movement calculated according to the dynamic model shows that the intensity of the surface roughness changes the higher the higher the circulation circulation rate and the smaller the effective forces acting in the load. Such modes are implemented in tanks that have a "rectangular" and "ellipsoid" cut. For finishing operations in vibratory finishing of parts, it is necessary to use tanks that have a "rectangular" with rounded transitions from the bottom to the walls and an "ellipsoid" transverse overcut.
Evaluation of virtual efficiency apparatus and welfare processing in reservoirs with multenergy impact and different form of transfer peripherals
Keywords: ефективність вібраційної обробки; багатоенергетичні технології; рух навантаження; фізична модель; vibration treatment efficiency; multi-energy technologies; loading movement; physical model